Synthesis and Characterization of Ba[CoSO]: Magnetic Complexity in the Presence of Chalcogen Ordering. Issue 30 (16th June 2015) - Valldor, Martin; Rößler, Ulrich K.; Prots, Yurii; Kuo, Chang‐Yang; Chiang, Jen‐Che; Hu, Zhiwei; Pi, Tun‐Wen; Kniep, Rüdiger; Tjeng, Liu Hao
Abstract Barium thio‐oxocobaltate(II), Ba[CoS2/2O2/2], was synthesized by the reaction of equimolar amounts of BaO, Co, and S in closed silica ampoules. The title compound (Cmcm, a=3.98808(3), b=12.75518(9), c=6.10697(4) Å) is isostructural to Ba[ZnSO]. The use of soft X‐ray absorption spectroscopy confirmed that cobalt is in the oxidation state +2 and tetrahedrally coordinated. Its coordination consists of two sulfur and two oxygen atoms in an ordered fashion. High‐temperature magnetic susceptibility data indicate strong low‐dimensional spin–spin interactions, which are suggested to be closely related to the layer‐type crystal structure and perhaps the ordered distribution of sulfur and oxygen. Antiferromagnetic ordering below TN=222 K is observed as an anomaly in the specific heat, coinciding with a significant lowering of the magnetic susceptibility. Density functional theory calculations within a generalized‐gradient approximation (GGA)+U approach identify an antiferromagnetic ground state within the square‐like two‐dimensional layers of Co, and antiferromagnetic correlations for nearest and next nearest neighbors along bonds mediated by oxygen or sulfur. However, this magnetic state is subject to frustration by relatively strong interlayer couplings.